2002
DOI: 10.1021/op025534u
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 1- and 2-(1-Hydroperoxy-1-methylethyl)naphthalenes on the Liquid-Phase Oxidation of Alkylaromatic Hydrocarbons

Abstract: The properties of 1-and 2-(1-hydroperoxy-1-methylethyl)naphthalenes as initiators were studied in the liquid-phase freeradical oxidation of hydrocarbons with oxygen. 2-(1-Hydroperoxy-1-methylethyl)naphthalene was found to initiate the reaction, whereas unexpectedly, 1-(1-hydroperoxy-1-methylethyl)naphthalene was found to inhibit the reaction. The products of decomposition of the studied hydroperoxides were found to exhibit essential differences. Thermal decomposition of 1-(1-hydroperoxy-1-methylethyl)naphthale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We have demonstrated that hydroperoxide 1b really acts as an initiator of free-radical oxidation of isopropylarenes. We have also shown that, in contradistinction to 1b , hydroperoxide 1a inhibits the free-radical oxidation of isopropylarenes with oxygen …”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…We have demonstrated that hydroperoxide 1b really acts as an initiator of free-radical oxidation of isopropylarenes. We have also shown that, in contradistinction to 1b , hydroperoxide 1a inhibits the free-radical oxidation of isopropylarenes with oxygen …”
Section: Introductionmentioning
confidence: 64%
“…The differential scanning calorimetry experiments showed that their thermal stabilities are similar; the temperatures of maximum rates of decomposition ( T max ) of the 1a and 1b are close to each other (197.5 and 193.6 °C, respectively) ), the other part of hydroperoxide 1a (about 50%) being converted to an unidentified dark tarry substance .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation